Structures of phytosterols and triterpenoids with potential anti-cancer activity in bran of black non-glutinous rice - Panawan Suttiarporn (2018)
© 2015 by the authors; licensee MDPI, Basel, Switzerland. Structures of some bioactive phytochemicals in bran extract of the black rice cv. Riceberry that had demonstrated anti-cancer activity in leukemic cell line were investigated. After saponification with potassium hydroxide, separation of the unsaponified fraction by reversed-phase high performance liquid chromatography (HPLC) resulted in four sub-fractions that had a certain degree of anti-proliferation against a mouse leukemic cell line (WEHI-3 cell), this being IC 50 at 24 h ranging between 2.80-467.11 µg/mL. Further purification of the bioactive substances contained in these four sub-fractions was performed by normal-phase HPLC. Structural characterization by gas chromatography-mass spectrometry (GC-MS), liquid chromatography-mass spectrometry (LC-MS) and nuclear magnetic resonance spectroscopy (NMR) resulted in, overall, the structures of seven phytosterols and four triterpenoids. Four phytosterols, 24-methylene-ergosta-5-en-3β-ol, 24-methylene-ergosta-7-en-3β-ol, fucosterol, and gramisterol, along with three triterpenoids, cycloeucalenol, lupenone, and lupeol, were found in the two sub-fractions that showed strong anti-leukemic cell proliferation (IC 50 = 2.80 and 32.89 µg/mL). The other sterols and triterpenoids were campesterol, stigmasterol, β-sitosterol and 24-methylenecycloartanol. Together with the data from in vitro biological analysis, we suggest that gramisterol is a significant anti-cancer lead compound in Riceberry bran extract.